2021
DOI: 10.3390/molecules26113139
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Down and Williams-Beuren Syndromes: An Overview

Abstract: Oxidative stress is the result of an imbalance in the redox state in a cell or a tissue. When the production of free radicals, which are physiologically essential for signaling, exceeds the antioxidant capability, pathological outcomes including oxidative damage to macromolecules, aberrant signaling, and inflammation can occur. Down syndrome (DS) and Williams-Beuren syndrome (WBS) are well-known and common genetic conditions with multi-systemic involvement. Their etiology is linked to oxidative stress with imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 86 publications
0
18
0
Order By: Relevance
“…A previous study revealed that DATS preserved cardiac function via decreasing oxidative stress and ER stress-mediated apoptosis ( Yu et al, 2017a ). SOD1 is an important enzyme against oxidative stress ( Ferrari and Stagi, 2021 ), which can be used to evaluate the level of oxidative stress in skin flaps. In the current study, the proteins SOD1, eNOS, and HO-1 that exert antioxidative stress effects and the level of GSH were increased by DATS treatment in flap tissue, indicating that DATS has antioxidant properties for flap survival.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that DATS preserved cardiac function via decreasing oxidative stress and ER stress-mediated apoptosis ( Yu et al, 2017a ). SOD1 is an important enzyme against oxidative stress ( Ferrari and Stagi, 2021 ), which can be used to evaluate the level of oxidative stress in skin flaps. In the current study, the proteins SOD1, eNOS, and HO-1 that exert antioxidative stress effects and the level of GSH were increased by DATS treatment in flap tissue, indicating that DATS has antioxidant properties for flap survival.…”
Section: Discussionmentioning
confidence: 99%
“…While a variety of diseases are reportedly associated with altered SOD1 activity, the following two hereditary diseases have attracted much attention. Because a trisomy of the 21st chromosome is the cause for Down's syndrome and SOD1 is mapped to the region where the putative causative gene is thought to be present, an elevation in SOD1 activity has been the suspected cause of Down syndrome [58]. Pathological abnormalities in the neuromuscular junctions in the tongue are characteristically observed in transgenic mice overexpressing SOD1 [59].…”
Section: Sod1mentioning
confidence: 99%
“…The etiology of this disease is associated with the induction of oxidative stress. The main contributing genes, including superoxide dismutase-1 and neutrophil cytosolic factor-1, are primarily involved in the regulation of the redox-state ( 5 - 7 ). WBSCR22 is localized on chromosome 7 (7q11.23) and constitutes an S-adenosyl-L-methionine (SAM) motif and nuclear localization signal with well-preserved features of methyltransferase family proteins ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%